Enzymatic homeostasis in peripheral blood lymphocytes in rats with dermatitis = Энзиматический гомеостаз в лимфоцитах периферической крови у крыс при дерматитах - Bereznyakova, A. I.; Cheremisina, V. F.; Mrozkowiak, M.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Bereznyakova A. I., Cheremisina V. F., Mrozkowiak M., Zukow W. Enzymatic homeostasis in peripheral blood lymphocytes in rats with dermatitis = Энзиматический гомеостаз в лимфоцитах периферической крови у крыс при дерматитах. Journal of Education, Health and Sport. 2015;5(11):203-216. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33850 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A203-216 https://pbn.nauka.gov.pl/works/669303 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. UDC 616.37-002-036.11 УДК 616.37-002-036.11 Enzymatic homeostasis in peripheral blood lymphocytes in rats with dermatitis Энзиматический гомеостаз в лимфоцитах периферической крови у крыс при дерматитах А. И. Березнякова1, В. Ф. Черемисина1, M. Mrozkowiak2, W. Zukow2 A. I. Bereznyakova1, V. F. Cheremisina1, M. Mrozkowiak2, W. Zukow2 1Национальный фармацевтический университет, г. Харьков 1National University of Pharmacy, Kharkiv 2Uniwersytet Kazimierza Wielkiego, Bydgoszcz 2Kazimierz Wielki University, Bydgoszcz Реферат В работе изучены нарушения энзиматического гомеостаза сапонин-перфорированных лимфоцитов периферической крови у крыс с дерматитами различной этиологии. Показано, что стимуляция лимфоцитов антигенами запускает каскад энергетически зависимых процессов, которые ведут к перераспределению макроэргов в клетке; это связано с достоверным снижением оуабаинчувствительной Na+, K+-АТФ-азной и Сa2+, Mg2+-АТФ-азной активности, уменьшением пула АТФ в лимфоцитах. Доказано, что при дерматитах различной этиологии, особенно аллергической природы, нарушаются регуляторные механизмы в лимфоцитах за счет перегрузки клеток Na+ и Сa2+, что приводит к энергодефициту лимфоцитов и нарушению их функциональной активности. Ключевые слова: энзиматический гомеостаз, лимфоциты, периферическая кровь, сапонин, РМСА – Са2+-АТФ-аза плазматической мембраны, SERCA – Ca2+-АТФ-аза саркоплазматического ретикулума. Summary We studied enzymatic disorders of homeostasis saponin-perforated peripheral blood lymphocytes in rats with dermatitis of various etiologies. It has been shown that the stimulation of lymphocyte antigens triggers a cascade of energy-dependent processes, which lead to a redistribution of macroergs in a cage; is associated with a significant decrease in ouabainsensitive Na+, K+-ATP-ase and Сa2+, Mg2+-ATP-ase activity, a decrease in the pool of ATP in lymphocytes. It is proved that the dermatitis of various etiologies, especially allergic nature violated regulatory mechanisms in lymphocytes due to overload Na+ и Сa2+, leading to disruption of the energy deficit lymphocytes and their functional activity. Tags: enzymatic homeostasis, cells, peripheral blood, saponin, RMSA - Са2+-ATPase of plasmic membrane, SERCA - Ca2+-ATPase of sarcoplasmic reticulum. Реферат ЕНЗИМАТИЧНИЙ ГОМЕОСТАЗ В ЛІМФОЦИТАХ ПЕРИФЕРИЧНОЇ КРОВІ У ЩУРІВ ПРИ ДЕРМАТИТАХ. В роботі вивчено порушення ензиматичного гомеостазу сапонін-перфорованих лімфоцитів периферичної крові у щурів з дерматитами різної етіології. Показано, що стимуляція лімфоцитів антигенами запускає каскад енергетично залежних процесів, які ведуть до перерозподілу макроергів у клітині; це пов’язано з достовірним зниженням оуабаінчутливої Na+, K+-АТФ-азної та Сa2+, Mg2+-АТФ-азної активності, зменшенням пулу АТФ в лімфоцитах. Доведено, що при дерматитах різної етіології, особливо алергічної природи, порушуються регуляторні механізми в лімфоцитах за рахунок перевантаження клітин Na+ і Сa2+, що призводить до енергодефіциту лімфоцитів і порушення їх функціональної активності. Ключові слова: ензиматичний гомеостаз, лімфоцити, периферична кров, сапонін, РМСА – Сa2+-АТФ-аза плазматичної мембрани, SERCA – Сa2+-АТФ-аза саркоплазматичного ретикулума.